Temperature and rainfall dependent mathematical modelling for progression of Zika virus infection. (24th May 2019) - Kumar, Narender; Faizan, Md Imam; Parveen, Shama; Dohare, Ravins
We formulated a susceptible-exposed-infected-recovered (SEIR) mathematical model for transmission of ZIKV. The model was used to estimate different parameters using the outbreak data obtained from Puerto Rico during 2015-2016 in this region. The inclusion of climatic factors in the model assisted in more realistic predictions of the transmission dynamics of ZIKV. The value basic reproduction number R 0 = 3.2869 calculated at estimated parameters suggested outbreak of infection in this region. The sensitivity analysis revealed that R 0 was highly influenced by death rate, mosquito biting rate and maturation rate of immature mosquitoes. The R 0 further implied that around 70% of the individuals should be immunised to develop herd immunity to prevent propagation of the disease. The simulation of controlled reproduction number revealed the values of different isolation coefficients ( ε 1 > 0.4, ε 2 > 0.14, τ 1 < 0.1). These coefficients might be utilised by policy makers in the control strategies against the infection.